Behavior problem: a panorama of the area (Brazilian Journal of Behavioral and Cognitive Therapy, 2003)
The terminology behavior problems brings serious difficulties due to its definition, classification and diagnostic, because it interferes not only with the analysis of the behaviors considered deviants but also the necessary interventions to avoid and/or terminate them either in the clinical or educational context. It is possible to verify the existence of distinctive groups of theorists employing the term behavioral problem. On one hand, there are the medical or biological model dealing with the subject primarily in terms of symptoms. On the other hand, there are authors that perceive the category in a more functional way, by evaluating not only behavioral deficits, but also behavioral precedents. One can assume, that an analysis of both views is possible through an unifying comprehension of the term, considering both, the indicatives of behavioral problems and its functional analysis. Therefore, this work has as its objective to present both views organized in relation to definitions, characteristics, determining factors, diagnostic, and treatment of the behavior problem category.